Effects of unweighting and speed on in-shoe regional loading during running on a lower body positive pressure treadmill - Smoliga, J. M.; Wirfel, L. A.; Paul, D.; Doarnberger, M.; Ford, K. R. (Journal of Biomechanics, 2015)
The purpose of this study was to determine how unweighted running on a lower body positive pressure treadmill (LBPPT) modifies in-shoe regional loading. Ten experienced runners were fit with pressure distribution measurement insoles and ran at 100%, 120%, and 140% of self-reported easy training pace on a LBPPT at 20%, 40%, 60%, 80%, and 100% body weight percentage settings (BWSet). Speeds and BWSet were in random order. A linear mixed effect model (p<0.05 significance level) was used to compare differences in whole foot and regional maximum in-shoe plantar force (FMAX), impulse, and relative load distribution across speeds and BWSet. There were significant main effects (p<0.001) for running speed and BWSet for whole foot Fmax and impulse. The model revealed 1.4% and 0.24% increases in whole foot FMAX (times body weight) and impulse, respectively, for every unit increase in body weight percentage. There was a significant main effect for BWSet on Fmax and relative load (p<0.05) for each of the nine foot regions examined, though four regions were not different between 80% and 100% BWSet. There was a significant (p<0.001) main effect for BWSet on forefoot to rear foot relative load. Linear relationships were found between increases in BWSet and increases in-shoe Fmax and impulse, resulting from regional changes in foot pressure which represent a shift towards forefoot loading, most evident <80% BWSet. Estimating in-shoe regional loading parameters may be useful during rehabilitation and training to appropriately prescribe specific speed and body weight levels, without exceeding certain critical peak force levels while running.